2017
DOI: 10.1158/2326-6066.cir-16-0288
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Survival and Clinical Benefit from Adoptive T-cell Transfer in Stage IV Melanoma Patients Is Determined by a Four-Parameter Tumor Immune Signature

Abstract: The presence of tumor-infiltrating immune cells is associated with longer survival and a better response to immunotherapy in early-stage melanoma, but a comprehensive study of the in situ immune microenvironment in stage IV melanoma has not been performed. We investigated the combined influence of a series of immune factors on survival and response to adoptive cell transfer (ACT) in stage IV melanoma patients. Metastases of 73 stage IV melanoma patients, 17 of which were treated with ACT, were studied with res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Hence, therapeutic vaccination can incite and modulate inflamed lesions so that the immune infiltration becomes more coordinated and the effector cells increase to similar or higher numbers when compared with healthy vulvar tissue. In this aspect, it does not differ from other T cellbased approaches, including adoptive T cell transfer 38 and checkpoint blockade 10 39 all of which have the best possible clinical impact when a tumor is inflamed or hot before start of therapy. The HPV16 SLP vaccine did not Open access Figure 5 Immune profile of non-responders (NR), partial responders (PR) and complete responders (CR) bases on the relative infiltration of significantly different immune cell subtypes and human papillomavirus (HPV)-specific T cell reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, therapeutic vaccination can incite and modulate inflamed lesions so that the immune infiltration becomes more coordinated and the effector cells increase to similar or higher numbers when compared with healthy vulvar tissue. In this aspect, it does not differ from other T cellbased approaches, including adoptive T cell transfer 38 and checkpoint blockade 10 39 all of which have the best possible clinical impact when a tumor is inflamed or hot before start of therapy. The HPV16 SLP vaccine did not Open access Figure 5 Immune profile of non-responders (NR), partial responders (PR) and complete responders (CR) bases on the relative infiltration of significantly different immune cell subtypes and human papillomavirus (HPV)-specific T cell reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…IF staining of CD68 and CD68 + CD163 + showed that the majority of macrophages belong to the M2 phenotype, suggesting a potential tumor-favorable environment created by macrophages in CM. As high cytotoxic T lymphocyte (CTL)/regulatory T cell (Treg) and high M1 (CD68 + CD163 - )/M2 macrophage ratios have been found to be associated with improved survival in breast cancer and cutaneous melanoma, respectively [ 14 , 18 ], we evaluated these ratios in our study. No significant difference in survival or association with clinical parameters was observed ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…32,33 However, almost no study assessed these ratios in melanoma, only one study assessed the prognostic role of CD8/Tregs ratio (Tregs were defined as CD3+ CD8-FOXP3+) HR 1.637 (0.956-2.801) for OS. 60 The last possible explanation for the favorable role of FOXP3+ TILs is that, FOXP3 is not specific for activated Tregs, it is needed to conjoint assess FOXP3 and additional markers, such as CD25. Regretfully, no study assessed this combination in melanoma, only two studies assessed the prognostic role of CD25 for OS by HR 1.8 (no 95% CI) (P= 0.68) 35 and two almost identical survival curves (P= 0.802).…”
Section: Discussionmentioning
confidence: 99%